Two Primary brain Tumurs in a patient with minimalComplaint a case report. - Khaliii, A- Hadi; Al-shalchy, Ali K. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Multiple tumors in the nervous system is a rare event.. Patient & Method: .A forty two years old male who was enjoying completely healthy life presented with one week history of a single attack of confusion .he was presented with double tumour in the brain operated up on our department by craniotomy. Results: His neurological clinical examination was negative. A CT scan & MRI of the brain showed two intracranial space occupying lesions. A solid right frontal lesion and another cystic lesion in the third ventricle. . The pathology proved the frontal lesion to be a meningioma while the third ventricular tumour was colloid cyst. Post operative period was uneventful. Follow up for few months showed no complaint. Conclution : Multiple Primary Tumor of the brain are uncommon & very to have a Meningioma assoaiated with colloid cyst of the 3rd ventnical in almost asymptomatic patimts.